The study of food, tourism, hospitality and events 21st-century approaches - Beeton, Sue; Morrison, Alison (Tourism, hospitality & event management., 2019)
This book elaborates upon, critiques and discusses 21st-century approaches to scholarship and research in the food, tourism, hospitality, and events trades and applied professions, using case examples of innovative practice. The specific field considered in this book is also placed against the backdrop of the larger question of how universities and other institutions of higher learning are evolving and addressing the new relationships between research, scholarship and teaching.